Analisis Kepemimpinan Transformasional Kepala Sekolah dalam Meningkatkan Etos Kerja Guru - Sri Andini; Rokhayani Yuslida Hannum Harahap; Amri Jamil Tanjung; Salma Tiaz (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The development of digital technology has brought significant changes in the field of education, especially in the learning process, school management systems, and teachers' work patterns. This situation requires school principals' leadership who can adapt, be innovative, and act as agents of change in improving teachers' work ethic. This study aims to analyze the role of school principals' transformational leadership in enhancing teachers' work ethic in the digital era and to examine its relevance to educational transformation. The research method used is a qualitative approach with a literature study type through the analysis of various journals and scientific sources from 2020–2025. The results of the study indicate that school principals' transformational leadership plays an important role in increasing teachers' motivation, commitment, and professionalism through ideal influence, inspirational motivation, intellectual stimulation, and individualized consideration. In addition, this leadership is also capable of creating a work culture that is collaborative, innovative, and adaptive to technological developments. Digital transformation in education not only involves the use of technology but also changes in work culture and the improvement of human resource competencies in schools. The implications of this research confirm that school principals as transformational leaders have a strategic role in the success of educational transformation in the digital era through the continuous enhancement of teachers' work ethic.